2020
DOI: 10.1007/s11012-020-01187-1
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting from the secondary resonances of a nonlinear piezoelectric beam under hard harmonic excitation

Abstract: This paper investigates the dynamical response of a nonlinear piezoelectric (PZT) energy harvester under a hard harmonic excitation and assesses its output power. The system is composed of a unimorph cantilever beam with a tip mass and exposed to an harmonic tip excitation with a hard forcing amplitude. First, the governing dimensionless nonlinear electromechanical ordinary differential equations (ODEs) are obtained. Next, the multiple scales method (MSM) is exploited to provide an approximate-analytical solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…To ascertain a better understanding of the harvester's working principles and performance dynamics, the way of polarization and polling conditions must keep in mind for a given PZT vibration-based nanogenerator. The mostly d 33 , d 31 , and sometimes d 15 modes of polarization for operation have been discussed in [31][32][33][34] depending upon how the force and the electric potential are related and the choice of one of these modes influences the maximum output voltage and power. Due to base and axial excitations, the power and voltage are increased because the device's natural frequency coincides with ambient frequencies while the energy of ambient vibration is distributed over a wide frequency spectrum.…”
Section:  Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To ascertain a better understanding of the harvester's working principles and performance dynamics, the way of polarization and polling conditions must keep in mind for a given PZT vibration-based nanogenerator. The mostly d 33 , d 31 , and sometimes d 15 modes of polarization for operation have been discussed in [31][32][33][34] depending upon how the force and the electric potential are related and the choice of one of these modes influences the maximum output voltage and power. Due to base and axial excitations, the power and voltage are increased because the device's natural frequency coincides with ambient frequencies while the energy of ambient vibration is distributed over a wide frequency spectrum.…”
Section:  Results and Discussionmentioning
confidence: 99%
“…The research showed that the power is produced of 16.3 mW at 219 Hz for 0.3N Stress. In [31], mechanically excited uni-morph piezoelectric membranes and electromechanical modeling are also studied. The maximum power produces for 80 N at 47 KΩ around 1.7 mW.…”
Section:  Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parametric resonance frequency is taken at the peak of the resonance as well. Figure 5(a) demonstrates that the superharmonic is moving with two frequencies [32,33]. The parametric resonance time history shows that the response is of similar frequency as the primary resonance, shown in figure 5(b).…”
Section: Model Case Component Considerationsmentioning
confidence: 93%